ANALISIS SISTEM INFORMASI AKUNTANSI PENERIMAAN KAS PADA RUMAH SAKIT ISLAM SUNAN KUDUS - Qurrotul Aini, Linda; Husnurrosyidah (Universitas Ratu Samban, 2023)
The research is aimed at analyzing the cash receipt accounting information system that has been used at the Islamic Hospital Sunan Kudus. The type of research used is descriptive qualitative research using interviews and observation techniques. The data analysis method used in this study refers to the method of data analysis that consists of three cycles of activity that occur simultaneously i.e. data reduction, data presentation, conclusion drawing or verification. The system includes working procedures, clarity of authority, and the liability of each department. The accounting system of cash receipts at the Sunan Kudus Hospital is obtained from various services such as payment of street care, hospital care, IGD room, clinic, and drug sales. Once the patient's payment is received by the hospital, it will be recorded on the receipt of the hospital cash. Accounting records ensure that all sales or transactions have been recorded in accordance with what happened and are supported by evidence of supporting documents.